2011
DOI: 10.4061/2011/321030
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Thyroid Hormones: Learning from Hypothyroidism

Abstract: Hypothyroidism induces several metabolic changes that allow understanding some physiopathological mechanisms. Under experimental hypothyroid conditions in rats, heart and kidney are protected against oxidative damage induced by ischemia reperfusion. An increased resistance to opening of the permeability transition pore seems to be at the basis of such protection. Moreover, glomerular filtration rate of hypothyroid kidney is low as a result of adenosine receptors-induced renal vasoconstriction. The vascular ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 110 publications
0
11
1
1
Order By: Relevance
“…Treatment of hyperthyroidism is important to prevent arrhythmic complications and even a subclinical hyperthyroid state should be treated, especially in high-risk patients. Another important point is prevention of iatrogenic hypothyroidism during treatment, because hypothyroidism also brings some other cardiovascular and general risks [ 98 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of hyperthyroidism is important to prevent arrhythmic complications and even a subclinical hyperthyroid state should be treated, especially in high-risk patients. Another important point is prevention of iatrogenic hypothyroidism during treatment, because hypothyroidism also brings some other cardiovascular and general risks [ 98 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Franco et al, 2011 [31] reported that hypothyroidism also could increase the formation of polyunsaturated fatty acids which in turn changed plasma membrane composition. Isman et al [28] and Hataya et al, [32] were in agreement with that explanation and reported that this change of lipid composition caused lipid peroxidation sensitivity in rats membranes with hypothyroidism and could decrease the vulnerability to oxygen radical which caused cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…The role of various hormones such as thyroid-stimulating hormone, cortisol, prolactin, and thyroid hormones in the pathogenesis of psoriasis has been studied previously. [ 7 ] The severity of the disease has been correlated with levels of thyroid hormones, since like prolactin, the thyroid hormone receptors are expressed in the skin[ 8 ] and their levels change during the active phase of disease and alleviation of the disease by antithyroid therapy.…”
Section: Introductionmentioning
confidence: 99%